How state ownership affects firms’ dividend payout: empirical evidence from Chinese listed companies - ZHANG, QING (2017)
This paper explores the state ownership’s impact on corporate dividend policy within Chinese context. Many ownership structure and dividend payout studies have revealed that agency theory plays a significant role in their research. In China many dividend researches’ results consistent with ‘tunneling’ effect, which implied the controlling shareholder may utilize dividend payout to expropriate interest through cash dividend. The paper examined 815 observations from Shanghai Stock Exchange with state ownership and cash dividend payout considered. Other possible explanatory variables such as foreign institutional investment, size, leverage are also estimated. The empirical result revealed a significant relationship between the ultimate controlling shareholder ownership and cash dividend payout ratio. Without other variables augmented, the State shares proportion also showed a positive correlation with cash dividend payout in simple regression model. This may consist with the tunneling hypothesis that controlling shareholder prefer cash dividend payout to generate more profit for themselves. Firm’s size also revealed a positive correlation with cash dividend payment. Although the Foreign institutional shareholding’s estimation showed no significant result in this research the influence of foreign shareholding on dividend payout has been discussed with other relevant studies’ findings. In general, this paper consisted with higher ultimate controlling shareholders’ ownership or state shareholders’ proportion may lead more cash dividend payout and many other researches revealed a mediate effect of foreign shareholding on tunneling effect or state ownership effect